EMG versus US: a randomized clinical trial comparing the efficacy in guiding botulinum toxin treatment in cervical dystonia - Graciani, Mayara Thouin; Costa, Flávio Henrique de Rezende; Rosso, Ana Lucia Zuma de; Salles, Gil Fernando (Arquivos de Neuro-Psiquiatria, 2025)
Botulinum toxin type A (BoNT-A) is considered the first-line therapy for cervical dystonia.To compare, in a randomized trial, the efficacy of treatment with BoNT-A guided by ultrasound (US) and electromyography (EMG) in patients with idiopathic cervical dystonia.A total of 40 patients (20 in each group; mean age: 54 years; 45% of female subjects; mean disease duration: 10.7 years) were randomized to either US- or EMG-guided BoNT-A treatment. The efficacy of BoNT-A was assessed through changes in the scores on the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS) before and 4 to 6 weeks after the treatment. The differences in the absolute and relative changes in the total TWSTRS scores and in its components (severity, incapacity, and pain) between the groups were evaluated.The US and EMG groups were well balanced in relation to baseline and demographic characteristics. After the BoNT-A treatment, there was a mean reduction in the TWSTRS score of 8 points (relative reduction of 23%) equally between the US and EMG groups (mean difference in absolute decrease of 0.1 point; p = 0.97; and mean difference in relative decrease of 2%; p = 0.89). There were no differences in the declines in the scores on the TWSTRS components, nor when the improvements in the TWSTRS scores were dichotomized as more significant or lower reductions (all p-values > 0.3).The present randomized trial did not demonstrate any difference in improvements between BoNT-A treatment guided by US or EMG in patients with idiopathic cervical dystonia.ReBEC Identifier: RBR-33dd4p4.
Keywords: Botulinum Toxins; Torticollis; Electromyography; Ultrasonography